Controlling molecular conformation for highly efficient and stable deep-blue copolymer light-emitting diodes - Hamilton,I; Chander,N; Cheetham,NJ; Suh,M; Dyson,M; Wang,X-H; Stavrinou,PN; Cass,M; Bradley,DDC; Kim,J-S (ACS Applied Materials and Interfaces, 2018)
We report a novel approach to the achievement of deep-blue, high-efficiency, and long-lived solution processed polymer light-emitting diodes (PLEDs) via a simple molecular-level conformation change whereby we introduce rigid β-phase segments into a 95% fluorene - 5% arylamine copolymer emission layer (EML). The arylamine moieties at low density act as efficient exciton formation sites in PLEDs whilst the conformational change alters the nature of the dominant luminescence from a broad, charge-transfer like emission to a significantly blue-shifted and highly vibronically structured, excitonic emission. As a consequence, we observe a significant improvement in Commission International de L'Eclairage (CIE) (x, y) co-ordinates from (0.149, 0.175) to (0.145, 0.123) whilst maintaining high efficiency and improving stability. We achieve peak luminous efficiency, η = 3.60 cd/A and luminous power efficiency, ηw = 2.44 lm/W; values that represent state of the art performance for single copolymer deep-blue PLEDs. These values are five-fold better than for otherwise-equivalent, β-phase poly(9,9-dioctylfluorene) (PFO) EML PLEDs (0.70 cd/A and 0.38 lm/W). This report represents the first demonstration of the use of molecular conformation as a vector to control the optoelectronic properties of a fluorene copolymer; previous examples have been confined to homopolymers.